Sei sulla pagina 1di 79

 L p L p C T ∈ L X

f : X −→ Y X Y X Y

X τ X X , X τ

A 1 ,

A α τ α A α τ

, A n τ = n =1 A k τ

k

τ X ( X, τ ) X

τ = {, X }

τ = P ( X ) P ( X ) X

( X, S ) ( Y, τ ) f : X −→ Y A τ f 1 ( A) ∈ S

( X, τ ) C ⊂ X

C τ τ 1 τ 2 X τ 1 τ 2 τ 2 τ 1 τ 1 τ 2 ( X 1 , τ 1 ) ( X 2 , τ 2 ) f : X 1 −→ X 2 τ 1 , τ 2 τ 1 τ 2 X τ 1 f : X 1 −→ X 2 τ 2

f : X 1 −→ X 2 { τ α } X α τ α

, X τ α α , X α τ α

a 1 , A 2

α τ α

A 1 A 2 α τ α

A 1 , A 2 τ α

α

A 1 A 2 τ α

α

 A σ σ A σ ∈ α τ α ⊂ α τ α ⇒ A σ ⊂ τ α ∀ α ⇒ σ A σ ∈ τ α ∀ α ⇒

F ⊂ P ( X ) X { τ α } F F ⊂ τ α τ F = α τ α F τ F F ( X ; τ ) x X E X E

¯

E E ( X, τ )

E x ( X ; τ ) U x x A x A U x E ( X, τ ) E U A E E A U

{ x k } ⊂ X { x k } x

U x k U k > k U x k U E X x X E U x E x

U E { x } =

E ( X, τ ) E x X U x E E E E E E

 T 1 − x, y, x, y, x = y A ∈ τ : x ∈ A, y ∈/ A T 2 − x = y A x , A y ∈ τ : x ∈ A x , y ∈ A y , A x ∩ A y = ∅

T 3 T 1 x F x A x , A F x F A x A F = T 4 T 1 F 1 , F 2 F 1 ; F 2

T 2 T 3 T 4

B ⊂ τ τ A τ x A B ⊂ B x B A B ⊂ τ x X A x B ∈ B x B A

X = d : X × X −→ R X d ( x, y ) 0, x, y X d ( x, y ) = 0 x = y d ( x, y ) = d ( y, x ) , x, y X d ( x, y ) d ( x, z ) + d ( z, y ) , x, y, z X

X ( X, d ) ( X, τ )

A X

x A r > 0 d ( y, x ) < r y A.

, X A 1 , A 2 A 1 A 2

x A 1 A 2 x A 1 , x A 2

B x,r 1 B x,r 2 A 1 A 2 .

A α α A α

x A α

α

x A α α

B x,r A α r

B x,r

A α .

α

B x,r = y | d ( x, y ) < r

T 2

x, y ( X, d ) , x = y d ( x, y ) = δ > 0 A 1 = B x, δ 2 A 2 = B y, δ 2 x B x, δ 2 , y B y, δ 2

B x, δ 2 B y,

δ

2

=

z B x, δ 2 , z B y, δ 2 d ( x, z ) <

δ

2

,

d ( z, y ) <

δ

2

d ( x, z ) + d ( z, y ) < δ

T 2 R n

d ( x, y ) = 1 x

h : ( X ; d X ) −→ ( Y, d Y )

= y

d Y h ( x ) , h ( y ) = d X ( x, y ) , x, y X.

( X, d X ) ( Y, d Y ) h : X −→ Y ( X, d ) ( X, d )

{ x k } ⊂ ( X, d ) ε > 0 k ε

h, k > k ε d ( x h , x k ) < ε.

( X, d ) X x X

X, d X Y, d Y X, d X Y, d Y

y k Y h : X −→ Y x k X x k = h 1 ( y k ) ( X, d X ) x = lim k x k y = h ( x )

d Y ( y, y k ) = d X ( x, x k )

y = lim

k →∞ y k

h : X, τ X −→ Y, τ Y h

X, τ X X, τ X

X, τ

A α X α A α A 1 ,

X N

Y, d Y

,

A N

k =1 A k

X, τ X Y, τ Y X, τ X Y, τ Y

B α τ Y Y

A α A α = h 1 B α h : X −→ Y h B α Y A α X

X, τ X A 1 , X

, A N A α

B k = h A k , k = 1 ,

, N

B α Y A 1 , X h Y, τ Y

,

A N

E X X, τ X E τ E

A E, A τ . E E A α τ E E X X, d E d : X × X −→ R E × E

X, d X X X

X, d { x k } ⊂ X { x k h } x X

X, d ε > 0 X ε

X { x k h } { x k } ⊂ X x X

d ( x, x k )

d ( x, x k h ) + d ( x k h , x k )

ε > 0 {x k } k ε

k, j > k ε d ( x j , x k ) < ε

>

2 . h ε k h

2 lim h d ( x, x k h ) = 0 h ε h > h ε d ( x, x k h ) < 2 ε

h ε h d ( x k h , x k ) < ε

> k ε

k > k ε , d ( x, x k ) < ε lim

k

x k = x

X X r > 0 r X x 1 X x 2 / B x 1 ,r

B x 1 ,r , B x 2 ,r X x 3 / B x 1 ,r

{ x k } ⊂ X

B x 2 ,r

d ( x h , x k ) r { x k } X

A α X

, B N

X B j X 1

A α X X 1 1 2 X 2 A α x k X k { x k } X

X B 1 ,

x = lim

k →∞ x k

A A α x A B x,r x r A X k k k B x,r A X k

A α X {x k } x X B x,r r > 0 B x,r X B x,r

, B x h ,r h

B x 1 ,r 1 ,

1

2

X 1 , X 2 K

T : X 1 −→ X 2

T ( αx + βy ) = αT ( x ) + βT ( y ) , α, β

K , x, y X 1

T : X 1 −→ X 2 L X 1 , X 2 X 1 , X 2 L X 1 , X 2 L X 1 , X 2 L L + ·

( i ) T + S ( x ) = T ( x ) + S ( x ) , T, S ∈ L , x X 1

( ii ) λT ( x ) = λT ( x )

λ K , T ∈ L .

X 2 = K T : X −→ K X L X, K X X L X, K X

X

X X X

X

X 1 = R n X 2 = R m A = ( a ij ) m × n

T ( x ) = A =

x

1

x

n

n

j =1 a 1 j x j

n

j =1 a mj x j

x R n ;

T : R n −→ R m T ∈ L R n , R m R n R m T ∈ L R n , R m

m = 1 T R n

X, · = C [0 , 1] , · C [0 , 1] u : [0 , 1] K

T u ( x ) = x u ( s ) d s,

0

T : X X T ∈ L ( X ) L ( X ) L ( X, X ) X 1 = X 2 T

T u T v ( x ) | u ( s ) v ( s ) | d s max ,1] | u ( s ) v ( s ) | = u v

0

s

[0

max x [0 , 1]

T

T u T v u v

X s [0 , 1]

T : X K

| T u T v | = | u ( s ) v ( s) | u v .

T X

T u = u ( s )

X 1 , · 1 , X 2 ; · 2 K T : X 1 X 2 T 0 X 1 T T X T

T : X 1 X 2 X 1 , · 1 X 2 ; · 2

sup

x

1

=0

T x 1 2

x 1 1

<

T = sup

x

1

=0

T x 1 2

x 1 1

T L X 1 , X 2

T ε = 1 δ > 0

x 1 1 < δ

T x 1 2 < 1

x 1 X 1 , x 1 = 0 y =

δ

2

x

1 1 x 1

T y 2 < 1

T x 1 2

T y 2

< 2

δ

x 1 1

y 1

=

T T < 2

δ

y 1

=

δ

2

T

T

T x 1 T x 2 2 T x 1 x 2 1

T x 1 2 T x 1 1

x 1 X 1 .

L ( X 1 , X 2 ) , ·

X 1 , · 1 , X 2 ; · 2 K

T = sup

x

1

=0

T x 1 2

x 1 1

K X 2 , · 2 L ( X 1 , X 2 ) , · K

T 0 T = 0 T x 1 2 = 0 x 1 T = 0 x 1 X 1 0 X 2 · 2

x 1 = 0 ( T + S ) x 1

2

T x 1 2 + Sx 1 2

x 1 1

x 1 1

x 1 1

T + S .

T k ⊂ L X 1 , X 2

T k x 1 T h x 1 2

T k T h

x 1 1

T k x 1 X 2 X 2 , · 2 lim k T k x 1 x 1 T : X 1 X 2

T T ( λx 1 + µ x 1 ) λT x 1 µT x 1 2

T x 1 = lim

k →∞ T k x 1

T ( λx 1 + µ x 1 ) T k ( λx 1 + µ x

1 ) 2 + | λ | T x 1 T k x 1 2 + | µ | T x 1 T k x 1 2 < ε.

T x 1 2 = lim

k

→∞

T k x 1 2 lim

k

T k x 1 1 M x 1 1

T k M T k M T L X 1 , X 2 lim k T T k = 0

T h x 1 T k x 1

2

x 1 1

T h T k

T x 1 T k x 1

2

x 1 1

lim T h T k

h

→∞

x 1 = 0 , x 1 X 1 .

T T k lim T h T k k

h

→∞

k → ∞

lim lim T h T k = 0

k →∞ h →∞

T k lim k T T k = 0

( X, · X ) K K X X

L p ( E ) , · p , p [1 , + ) v L q q p F : L p R

F ( u ) = F uv ,

u L p .

F L p ( E ) F v q F = v q

L p | u¯ | p = | v | ( q 1) p = | v | q u = u¯

u¯ = v | v | q 1 .

F ( u ) v q u p

u¯ p = v q/p

q

 F (¯u ) = F (¯u ) = | v | q u¯ p u¯ p v q/p q

= v q q/p

q

=

v q

F v q F = v q ( L p ) p [1 , + ) ( L p ) v L q

( L ) v L 1

X 1 , · 1 , X 2 , · 2 K

L ( X 1 , X 2 ) = L ( X 1 , X 2 ) X 1

X 1 N

, x N } X 1 T ∈ L ( X 1 , X 2 )

{ x 1 ,

λ k = ( λ k ,

, λ N ) K N x k =

k

N

i =1 λ i

k

1

x i

T x k 2 k , x k 1 = 1 .

k

N

i =1

λ

k

i

T x i 2 C λ k N .

µ K N

N

i

=1

µ

i x i

µ = lim

k

→∞

1 = lim

k

→∞

λ k

λ k N

, µ N = 1 .

N

i =1 λ i

k

x i 1

λ k N

1

lim k = 0

k

→∞

{ x 1 ,

, x N } X 1

X { x } ⊂ X

, { x }

{ x 1 , x 2 ,

x n } ⊂ { x } x 1 ,

,

x

n

{x } { y }

{ x } ⊂ { y } .

( E, ) G E g 1 , g 2 G

g 1 g 2 g 2 g 1 .

( X, ) { x }

Y X z X

y z, y Y .

z = Y